2010
DOI: 10.1111/j.1365-2958.2009.06959.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential role for ESAT6 in dissemination ofM. tuberculosisvia human lung epithelial cells

Abstract: SummaryESAT6 has recently been demonstrated to cause haemolysis and macrophage lysis. Our studies demonstrate that ESAT6 causes cytolysis of type 1 and type 2 pneumocytes. Both types of pneumocytes express membrane laminin, and ESAT6 exhibits dosedependent binding to both cell types and to purified human laminin. While minimal ESAT6 was detected on the surface of Mycobacterium tuberculosis grown in vitro, exogenously provided ESAT6 specifically associated with the bacterial cell surface, and the bacterium-asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
114
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(120 citation statements)
references
References 56 publications
6
114
0
Order By: Relevance
“…However, it also involves in the virulence and pathogenicity of MTB (Boggaram et al 2013). Based on its ability of binding to laminin and causing lysis of lung epithelial cells, it is suggested that ESAT-6 plays a role in the dissemination of MTB (Kinhikar et al 2010). ESAT-6 also regulates cytokine production through immune cells, such as induction of IL-1 secretion by macrophages (Mishra et al 2010) and inhibition of IFN-γ production by T-cells (Peng et al 2011), indicating that it may greatly influence the innate and adaptive immune responses to MTB infection.…”
Section: Introductionmentioning
confidence: 99%
“…However, it also involves in the virulence and pathogenicity of MTB (Boggaram et al 2013). Based on its ability of binding to laminin and causing lysis of lung epithelial cells, it is suggested that ESAT-6 plays a role in the dissemination of MTB (Kinhikar et al 2010). ESAT-6 also regulates cytokine production through immune cells, such as induction of IL-1 secretion by macrophages (Mishra et al 2010) and inhibition of IFN-γ production by T-cells (Peng et al 2011), indicating that it may greatly influence the innate and adaptive immune responses to MTB infection.…”
Section: Introductionmentioning
confidence: 99%
“…ESAT-6 has recently been demonstrated to cause haemolysis and macrophage lysis and also causes cytolysis of type 1 and type 2 pneumocytes. Since both types of pneumocytes express membrane laminin, and ESAT-6 exhibits dose-dependent binding to purified human laminin, these observations suggest that the specific association of ESAT-6 with the bacterial surface is mediated thought laminin (Kinhikar et al, 2010).…”
Section: Early Secretory Antigenic Target (Esat-6) (Rv3875) or Esxa Pmentioning
confidence: 84%
“…These predicted vaccine candidates are proteins predicted as adhesins and adhesin-like proteins using SPAAN at P ad [ 0.6 (Sachdeva et al 2005) and screening for putative extracellular or surface localization characteristics using PSORTb v.3.0 (Yu et al 2010). A slightly lower P ad value of 0.6 instead of 0.7 (Sachdeva et al 2005) was used with SPAAN to include the well known mycobacterial adhesin Heparin Binding Hemagglutinnin (HBHA) across the selected pathogenic mycobacterial genomes (Menozzi et al 1998) along with other characterized host cell binding proteins such as ESAT-6, Antigen 85A, Antigen 85B and Antigen 85C (Kinhikar et al 2010;Armitige et al 2000). The allowance of this slight relaxation was favored to increase the likelihood of mycobacterial adhesins being predicted.…”
Section: Rationalementioning
confidence: 99%